Consumer perception and sensory profiling of cassava mealiness attributes using hedonic, JAR, and CATA methods - Osunbade, A.O.; Alamu, E.O.; Awoyale, W.; Adesokan, M.; Nwaoliwe, G.; Akinwande, B.; Adejuyitan, A.; Lungaho, M.; Maziya-Dixon, B. (2025)
The ability of cassava root to be softened within a short period, being easy to chew, and dissolving easily upon biting, otherwise known as cassava root mealiness, is one of the major attributes of boiled cassava roots. This study aimed to identify the attributes of cassava root mealiness from consumers' end and evaluate consumer acceptability of boiled cassava roots. A well-structured questionnaire comprising of a 9-point hedonic, Just About Right (JAR) and Check-All-That-Apply (CATA) test was administered to 120 respondents to elicit information on cassava root mealiness (CRM) attributes and to evaluate four cassava varieties (danwarri, suppi, akpu, dangbo) for consumers' acceptability of boiled cassava in the selected LGAs of Benue State, Nigeria (Vandekya, Ushongo, Konshisha and Gwer East) using purposive sampling techniques. Data collected were subjected to Analysis of Variance (ANOVA) using statistical packages for social science (SPSS) and XLSTAT packages. CRM for the four cassava root varieties were dissolving easily, easy to chew, and softness. The CATA test showed that the most important mealiness attributes of boiled cassava roots were dissolving easily (80%) > being easy to chew (78%) > being moderately soft (76%). The JAR test results also revealed that the softness and chewiness of danwarri and suppi cassava varieties scored above 50%, just about right (JAR) values. The acceptability test showed that danwarri variety was scored 7.48 > suppi (6.68) > akpu (5.44) > dangbo (4.19) in that order. This information, with an in-depth laboratory characterization of the raw roots, will assist breeders in developing improved cassava varieties that are mealable and acceptable to the consumers.